Metabolic modulation-driven self-reinforcing pyroptosis-STING nanoadjuvant for potentiated metalloimmunotherapy - Linzhu Zhang; Di Wang; Yiming Liu; Nailin Yang; Shumin Sun; Chunjie Wang; Duo Wang; Jihu Nie; Juan Qin; Lei Zhang; Liang Cheng; Haidong Zhu (Bioactive Materials, 2025)
Pyroptosis is a critical process that triggers inflammatory responses and mitochondrial DNA (mtDNA) release, thereby activating the cGAS-STING pathway. However, tumor metabolism, particularly glycolysis, often suppresses immune activation. To address this, we developed GOCoF2, a self-amplifying pyroptosis-STING nanoadjuvant that integrates glucose oxidase (GOx) with cobalt fluoride (CoF2) nanoenzymes. This nanoadjuvant excelled in converting intratumoral H2O2 into reactive oxygen species (ROS), inducing cell pyroptosis. Its self-sustaining mechanism involved glucose depletion and continuous H2O2 generation, ensuring persistent catalytic activity. This metabolic manipulation and induction of oxidative stress significantly enhance pyroptosis in tumor cells. The released mtDNA subsequently activated the cGAS-STING pathway, with Co2+ further amplifying this effect. Notably, glucose-dependent TREX2 inhibition intensified cGAS-STING activation through metabolic regulation, leading to a strong immune response and tumor growth suppression. When combined with immune checkpoint blockade therapy, GOCoF2 significantly inhibited primary and distant tumor progression via systemic immune activation. Additionally, we formulated GOCoF2-lipiodol for transarterial embolization, which demonstrated superior efficacy in a rat model of orthotopic hepatocellular carcinoma. This study not only sheds light on the intricate relationship between tumor metabolism and immune regulation but also introduces a novel therapeutic approach for hepatocellular carcinoma.